The Effect of Modified Floor Reaction Ankle Foot Orthosis on Walking Abilities in Children with Cerebral Palsy: A Case Study - Mahmoud Bahrami-Zadeh; Mokhtar A'razpour; A'tefeh Aboutorabi; Mohammad Reza Azarpira (University of Social Welfare and Rehabilitation Sciences, 2015)
Objective: This study was designed to evaluate the effectiveness of a modified Floor Reaction Ankle Foot Orthosis (FRAFO) design on gait performance in boy with cerebral palsy. Materials & Methods: In this study, one boy with diplegic cerebral palsy (CP) wore a modified FRAFO bilaterally for six weeks. Immediate effectiveness of the orthosis on improving gait and also following six weeks of gradual orthosis use were recorded. Primary outcome measures were walking speed, cadence and stride length, plus hip, knee and ankle joints range of motion that recorded by VICON motion analysis system. Results: Cadence, stride length and walking speed were all increased when the Boy with CP wore the modified FRAFO. The boy demonstrated a reduction in ankle ROM when using the modified FRAFO. The mean knee joint ROM was increased from 36.8±13.72 degrees when walking with an orthosis at baseline to 43.0±1.10 degrees when walking with an orthosis after six weeks of use. Boy with the modified FRAFO also had decreased hip flexion angle at initial contact and an extension shift during stance phase following 6 weeks of orthosis use compared to when initially donning it. Conclusions : A modified FRAFO can improve gait parameters in children with cerebral palsy.